COVID‐19‐related psychiatric impact on Italian adolescent population: A cross‐sectional cohort study. Issue 5 (29th March 2021) - Mensi, Martina M.; Capone, Luca; Rogantini, Chiara; Orlandi, Marika; Ballante, Elena; Borgatti, Renato
Abstract: We investigated the prevalence rate and sociodemographic correlates of COVID‐19‐related posttraumatic stress disorder (PTSD), and COVID‐19‐related acute stress disorder (ASD) among Italian adolescents, their level of stress, perception of parental stress, and connection with mental health. Adolescents aged 12–18 years compiled an online questionnaire designed through validated diagnostic instruments. We enrolled 1262 adolescents who declared that they had not experienced any previous traumatic events. Participants were divided into two groups: 118 adolescents with psychiatric problems (APP+) and 1144 without (APP−). In total, 79.52% reported isolated COVID‐19‐related ASD (29.48%) or PTSD symptoms (50.04%). One adolescent met the diagnosis of COVID‐19‐related ASD and two met the diagnosis of COVID‐19‐related PTSD, according to DSM‐5. Adolescents with subthreshold COVID‐19‐related ASD and PTSD symptoms referred the highest levels of personal stress and adolescents with psychiatric/psychological conditions experienced higher stress. Health measures should be urgently employed prioritizing psychosocial stressors among adolescent population.